Protocol validation for care of patients with pulmonary hypertension (Research, Society and Development, 2022)
Introduction: Pulmonary hypertension is a serious disease defined by increased pressure in the pulmonary vessels. It is a clinical syndrome due to increased pulmonary vascular resistance, which occurs due to vasoconstriction and/or degeneration of the vascular bed of the lungs, causing progressive loss of gas exchange capacity. The need for the development and validation of a care protocol for patients with pulmonary hypertension admitted to intensive care units is pointed out through evaluation by specialists of items that are believed to be relevant. Objective: To develop and validate a care protocol for patients with pulmonary hypertension in intensive care units. Method: This is a methodological study to validate the content of a care protocol for patients with pulmonary hypertension, through the application of the Delphi technique, based on Spinola's theoretical framework. Results:Twenty professionals were invited to participate in the evaluation of the instrument, and 13 agreed to participate; however, 9 evaluators participated in the first Delphi Round. The final construct remained with 4 topics and 23 items, and no item was removed after evaluation by the experts. Conclusion: The protocol for care ofpatients with pulmonary hypertension is a practical instrument and aims to ensure patient safety and the quality of care provided in conjunction with technological advances. It is believed that the protocol will help multidisciplinary teams to promote safe, accurate and efficient care for patients with pulmonary hypertension in intensive care units.